Role of Initial and Follow-up LDH Titer in COVID-19 Pneumonia: A Single Center Experience of 2000 Cases in Tertiary Care Setting in India (Journal of Medicine, 2023)
Introduction: Robust data of LDH (Lactate dehydrogenase) is available in bacterial infection, and it can be utilized in this COVID-19 Pneumonia pandemic for initial assessment, planning of treatment in indoor setting in association with HRCT severity.Methods: Prospective, observational, 12 weeks follow up study, included 2000 COVID-19cases confirmed with RT PCR. All cases were assessed with lung involvement documented and categorized on HRCT thorax, oxygen saturation, LDH at entry point and follow up. Age, gender, comorbidity and BIPAP/NIV use and outcome as with or without lung fibrosis as per CT severity. Statistical analysis is done by Chi square test.Results: HRCT severity score at entry point has significant correlation with LDH titer [p